Clinical Case Clinical presentation of secondary syphilis in HIV-infected patients - Larisa I. Glebova; Ekaterina V. Zadionchenko; Anna V. Shalaginova (LLC "MEDIAFORMAT", 2024)
Predominantly sexually transmitted infections (STIs) continue to be of concern to physicians. Particularly interesting are cases of combined STIs. Patients infected with human immunodeficiency virus (HIV) and other diseases pose the most challenging diagnostic and treatment scenarios. Venereologists observe severe manifestations of chronic dermatoses in individuals with HIV infection, atypical courses of other infections, and lack of response to conventional treatment methods. This study focuses on monitoring HIV-infected patients with syphilis during their hospitalization in the venereology department of the V.G. Korolenko Clinic, a branch of the State Budgetary Healthcare Institution Moscow Research and Practical Center for Dermatovenerology and Cosmetology. The study presents a differential diagnosis of secondary syphilis manifestations in these patients and discusses the peculiarities of the disease course.